(3GdMceI aj NhGU GdCMLGQs - (3CMeO Hf jhSa GdJjaGTj, TgGH GdOjf CHh GdYHGS,J (B651 (3g` s
(3ChdgG (B:s
(3gPG cJGH ZQjH GdhVY YLjH GdLeY YXje GdfaY s
(3BNQgG (B:s
(3GfJgi cJGH GdMceI ai NhGU GdCMLGQ s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(100 d) s
Keywords: (3GdcjejGA h GdWHjYjGJs